Performance Optimization of Image Cryptography for Copyright Protection on High-Resolution Images Using the Hill Cipher with Flexible Matrix Keys - Miftakhul Rohman; Abd. Charis Fauzan; Veradella Yuelisa Mafula (Universitas Pancasakti, 2026)
The increasing use of high-resolution digital images has raised serious concerns regarding copyright protection and unauthorized distribution. Image cryptography is one of the effective approaches to safeguard visual data by transforming images into unintelligible forms. The Hill Cipher algorithm, which is based on matrix operations, has potential for image encryption; however, its application to high-resolution images often suffers from high computational cost. This study proposes a performance optimization of image cryptography for copyright protection by exploiting the flexibility of matrix key sizes in the Hill Cipher algorithm. The optimization focuses on improving computational efficiency without modifying the fundamental cryptographic mechanism. Experiments were conducted on high-resolution images using different matrix key sizes (2×2, 3×3, and 4×4). Performance was evaluated in terms of encryption and decryption time, while security robustness was assessed using Entropy, Number of Pixel Change Rate (NPCR), and Unified Average Changing Intensity (UACI). The experimental results demonstrate that increasing the matrix key size significantly reduces the total computation time, achieving up to nearly 50% performance improvement, while maintaining high security levels. The encrypted images exhibit entropy values close to the ideal level, NPCR values above 99%, and stable UACI values, indicating strong randomness and diffusion properties. These findings confirm that the proposed optimization improves computational performance without compromising cryptographic security. Therefore, the optimized Hill Cipher remains effective and suitable for copyright protection of high-resolution images.